Effect of sous vide cooking parameters on physicochemical properties and free amino acids profile of chicken breast meat - Nyam, Kar Lin; Goh, Kok Ming; Chan, Shu Qin; Tan, Chin Ping; Cheong, Ling Zhi (Elsevier, 2023)
The combined effects of brining (0% and 3% NaCl) and sous vide treatment (45, 90 and 135 min at 60 or 70 ℃) to the physicochemical properties, textural, microbiological and free-amino acids (FAA) released were evaluated using chicken breast meat. Results showed that the sous vide method produced chicken breast meat with a soft texture without affecting the pH, water activities, cooking loss, moisture content, and colour attributes. Brine treatment was effective to reduce microbial load. Brine treatment also effective to reduce the FAA loss from chicken breast meat samples during sous vide cooking. Total FAA loss from the brined sample was generally half (16.70–36.80 mg/100 g) of the non-brined samples. The glutamic acid loss was lower at 2.57 mg/100 g after brining. Overall, brine treatment combined with sous vide prevents FAA loss in chicken breast meat while maintain or improve the qualities.